TEX264-mediated selective autophagy directs DNA damage repair - Qi, Yuxia (2025)
DNA is constantly subject to damage from endogenous and exogenous factors, leading to mutations and disease. While DNA is traditionally repaired in the nucleus, Lascaux et al. reveal a novel role for the lysosome in DNA repair, demonstrating that topoisomerase 1 (TOP1) cleavage complex (TOP1cc) DNA lesions are degraded via TEX264-mediated selective autophagy.